The design of the patella os with wireframes in the direction of the coordinate axes utilizes a multilayer strategy - Kurniawan, Wahyudi (IHSA Institute, 2022)
Osteology is the science of anatomy in the field of medicine, which includes studying the structure and shape of bones, especially the anatomy of human bones. One of the learning methods is observing and analyzing human bone replicas, this requires that the design of the bone replicas must be similar to the original form. Model design using computer technology, namely CAD (Computer Aided Design) and CAM (Computer Aided Manufacturing) is now widely used in the field of design and engineering. Complex and precise modeling can be done in a short time with uniform results. PowerSHAPE software as a CAD application program is capable of creating complex and precise models. By using multiple layers, The patella bone wireframe produced by the rapid prototyping method can be processed easily so that it is hoped that a replica of the patella bone can be made close to its original shape. From the design results, molds and machining simulations can be made using the CAM application program, namely PowerMILL software.